ANALISIS NATRIUM SIKLAMAT PADA TEH JUMBO DI KABUPATEN GROBOGAN DENGAN METODE KUALITATIF DAN KUANTITATIF - iman cahyani_putri; Maulita Saraswati; Wahyu Purwanjani (Universitas An Nuur, 2025)
Background: Jumbo tea is a popular drink because it is practical and affordable. However, manufacturers often add sodium cyclamate, an artificial sweetener that is 30 times as sweet as sucrose and is known to be cheap, to reduce production costs. Excessive use of sodium cyclamate can cause health problems. Purpose: This research aims to analyze the presence and levels of sodium cyclamate in jumbo tea drinks circulating in Grobogan Regency. Method: This research used 10 jumbo tea samples taken from 5 sub-districts in Grobogan Regency using a purposive sampling method, namely samples that had an excessively sweet taste. Analysis was carried out qualitatively using the deposition method and quantitatively using the UV-Vis Spectrophotometry method. Results: Of the 10 samples tested, the qualitative test results showed that 3 samples were positive for containing sodium cyclamate (samples C2, E1, and E2) which were characterized by the formation of a white precipitate. The quantitative test results on the three positive samples showed the following sodium cyclamate levels: sample C2 was 0.08104 g/kg, sample E1 was 0.04693 g/kg, and sample E2 was 0.06242 g/kg. Conclusion: There were 3 out of 10 jumbo tea samples in Grobogan Regency that tested positive for sodium cyclamate15. However, the sodium cyclamate levels found in the three samples were still below the maximum limit permitted by BPOM (3 g/kg).